Practical petrophysics - Kennedy, Martin (Petroleum engineering consultant) (Elsevier, 2015)
Practical Petrophysics looks at both the principles and practice of petrophysics in understanding petroleum reservoirs. It concentrates on the tools and techniques in everyday use, and addresses all types of reservoirs, including unconventionals. The book provides useful explanations on how to perform fit for purpose interpretations of petrophysical data, with emphasis on what the interpreter needs and what is practically possible with real data. Readers are not limited to static reservoir properties for input to volumetrics, as the book also includes applications such as reservoir performance, seismic attribute, geo-mechanics, source rock characterization, and more.
Keywords: Petroleum -- Geology.; Petrology.; Petroleum engineering.; Geophysics.; elektronické knihy; electronic books